The Impact of Accounting Reforms in Financial Reporting- Case of Albania - Miti, Mirela Ujkani; Dhamo, Sotiraq (European Journal of Economics and Business Studies, 2018)
In the line with Albania's membership in the European Union, as in many other countries, we have been implementing reforms in the accounting field, which have had an impact on financial reporting. These reforms have also affected the accounting profession. The establishment of a full set of National Accounting Standards (NAS) in accordance with IFRS was the main basis of these reforms. Through our study, following a review of the literature and focusing on the National Accounting Council's objective in updating national accounting standards in the context of harmonization with European Parliament Directive 2013/34 / EU (hereafter referred to as the "Directive"), we will highlight if this harmonization in itself is essential and effective for the economic unit, or it is simply an update. Based on the analysis of the primary data through the fuzzy logic analysis method, the effect of the accounting reform in the financial reporting will be studied by observing the relationship that may exist between these two indicators, as well as measuring the convergence level and making the difference between the adjusted NAS and the previous set of them.
Keywords: financial reporting, accounting standards, legal framework, formal harmonization, Measurement.